Faktor-faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor - Nirajenani, Cokorda Istri Putra; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2018)
This study aims to obtain empirical evidence on the influence of taxpayer awareness, service quality, understanding tax laws, taxation sanctions and tax dissemination on taxpayer compliance in paying motor vehicle tax at SAMSAT Gianyar office. The theory used in this research is Theory of Planned Behavior. The number of samples examined were 100 motor vehicle taxpayers. The method of determining the sample using accidental sampling, which takes the respondent as a sample by chance. Data collection was done through questionnaires. The analysis technique used is multiple linear regression analysis. Based on the analysis, it can be concluded that the awareness of taxpayers, the quality of service, the understanding of taxation regulations, taxation sanctions and tax socialization have a positive effect on taxpayer compliance in paying motor vehicle tax at SAMSAT Gianyar office.